PlayMaps - Representation of 3D cartography data in Augmented Reality (AR) games - Filipe Carlos de Almeida Duarte da Cunha Nogueira (2023)
The present dissertation has, as its theme, the representation of 3D cartography data in Augmented Reality (AR) environments applied to mobile technologies. In tourism, choosing a place to visit can be a hard and exhaustive process which most times brings unforeseen setbacks. Given the abundance of information about a location, or even the lack thereof in many circumstances, it's simple for a possible tourist to become disoriented and make the incorrect judgement of not visiting it. In many cases, people even are unaware of the regions' potential. Many city officials and space marketers have struggled to find ways to attract more tourists to their cities, often asking themselves, "How can I promote my city to the world in a more effective way?". Obviously, this advertisement needs to be done in a safe and affordable way. Therefore, this dissertation aims to create a game for teens, between 10 and 15 years old, based on Augmented Reality (AR), which is capable to digitise a paper map and allowing the user to interact with it. The app will have to provide the educational component of the territory and also an appropriate level of interaction with the user. This app will be easy to use, user-friendly and compatible with any mobile operating system. As such, it is designed that anyone with a smart phone can use this technology. Furthermore, this app will be flexible, adaptable and generic. Different cartographies will require different geographical models or even different game methodologies. Therefore, this application will have the ability to import different geographic information, and create a specific game to that cartography. Two previous studies were carried out in this area, namely to enhance the experience of visits to Galeria da Biodiversidade and Jardim Botânico as a form of a game. The first study employs the case study method, using a quantitative and qualitative approach to comprehend how the entertaining experience given by augmented reality technology may contribute in the delivery of the information these spaces intend to transmit to visitors {soares2021flo}. The second study sought to explore ways to connect indoor and outdoor environments through Augmented Reality (AR) {teixeira2021serious}. These types of approaches on how to disseminate information are fundamental for the user to have an appropriate grasp of what the region has to offer. These functionalities will be applied to cartography of know territories in order to investigate ways to promote tourism by improving and innovating the way people learn and explore new cities and other spaces. Although this dissertation is only a case study, with this implementation, the proposed solution can become a stepping stone to the development of a universal tool for any institution and/or city that intends to promote itself.